Role of Inhibin B and Ratio of Luteinizing: Follicle-Stimulating Hormones in Phenotyping Polycystic Ovarian Syndrome - Falh, Zainab G.; Saleh, Basil O.; Al Naddawi, Afraa M.; Mohammed, Ghada (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Polycystic ovary syndrome is among the leading causes of fertility-related problems and menstrual irregularities in women of reproductive age. The granulosa cells of the developing pre-antral and antral follicles produce inhibin B, which triggers chemical responses in the ovaries. Inhibin B is most often observed in the follicular phase when levels peak early and then decline over time Objectives: This study was designed to investigate the role of serum inhibin B and the Luteinizing Hormone / Follicle Stimulating Hormone ratio in differentiation between the different phenotypes of polycystic ovary syndrome as well as to define the predominant PCOS phenotype. Methods: This cross-sectional research was conducted in the Department of Biochemistry, College of Medicine, University of Baghdad from November 2023 to March 2024. The study included 111 women, ranging in age from 18-40 years. Among these, 91 women were diagnosed with polycystic ovary syndrome (PCOS) based on the 2003 Criteria for the Rotterdam Consensus, and the other 20 were healthy women. Investigations included serum levels of inhibin B using the Enzyme-Linked Immunosorbent Assay technique, follicle Stimulating Hormone, luteinizing Hormone and prolactin using Tosoh AIA-2000 Automated Immunoassay, to calculate the LH/FSH ratio. Results: phenotype A was observed to be the predominant PCOS phenotype, while phenotype B was the rare form. The mean ±SEM values of the inhibin B levels for the phenotypes B (26.07±0.23 pg/ml, p=<0.001), C (25.96±1.68 pg/ml, p=<0.0001), and D (37.51±2.31 pg/ml, p=<0.0001), respectively, were significantly lower than those of the control women (57.68±2.07 pg/ml). However, the mean ±SEM value of inhibin B of phenotype A (50.46±7.12 pg/ml) was comparable to that of controls. The mean value of the LH levels of phenotype A (7.12±0.76 µIU/ml) showed significantly higher numbers than those of the control women (4.59±0.38 µIU/ml, p=0.03). Furthermore, the mean values of the LH/FSH ratio were significantly elevated in phenotypes A (p=0.001) and B (p=0.04) as compared to the controls. Conclusion: Serum Inhibin B level and LH/FSH ratio can be used to distinguish between the different phenotypes of PCOS.